Students’ Errors in Mathematical Problem-Solving Ability on the Triangular and Quadrilateral Materials at Junior High Schools (SMP) Jakarta - Asriyani, Rosida Yahya; Handayani, Isnaini; Hadi, Windia (Universitas Islam Negeri Raden Intan Lampung, 2020)
This research was aimed to analyze student's errors on triangular and quadrilateral material in terms of problem-solving ability. This research was motivated by the low problem-solving ability and errors often made by students during the mathematics learning. The research approach was descriptive-qualitative that was done by analyzing the students' difficulty in solving description problems. The techniques of data collection were observation, learning outcomes tests, and interviews. The data were analyzed qualitatively based on Newman Error Analysis. Based on the results of the research, it was found that students' reading errors were in the high, medium, and low categories. Students' comprehension errors were in the medium and low categories, students' transformation errors were in the high, medium, and low categories, students' process skills errors were in the high, low, and medium categories and students writing errors (encoding error) were in the high, medium, and low categories.